Variation-Tolerant Capture and Multiplex Detection of Nucleic Acids: Application to Detection of Microbes - Öhrmalm, Christina (American Society for Microbiology, 2012)
In contrast to ordinary PCRs, which have a limited multiplex capacity and often return false-negative results due to target variation or inhibition, our new detection strategy, VOCMA (variation-tolerant capture multiplex assay), allows variation-tolerant, target-specific capture and detection of many nucleic acids in one test. Here we demonstrate the use of a single-tube, dual-step amplification strategy that overcomes the usual limitations of PCR multiplexing, allowing at least a 22-plex format with retained sensitivity. Variation tolerance was achieved using long primers and probes designed to withstand variation at known sites and a judicious mix of degeneration and universal bases. We tested VOCMA in situations where enrichment from a large sample volume with high sensitivity and multiplexity is important (sepsis; streptococci, enterococci, and staphylococci, several enterobacteria, candida, and the most important antibiotic resistance genes) and where variation tolerance and high multiplexity is important (gastroenteritis; astrovirus, adenovirus, rotavirus, norovirus genogroups I and II, and sapovirus, as well as enteroviruses, which are not associated with gastroenteritis). Detection sensitivities of 10 to 1,000 copies per reaction were achieved for many targets. VOCMA is a highly multiplex, variation-tolerant, general purpose nucleic acid detection concept. It is a specific and sensitive method for simultaneous detection of nucleic acids from viruses, bacteria, fungi, and protozoa, as well as host nucleic acid, in the same test. It can be run on an ordinary PCR and a Luminex machine and is suitable for both clinical diagnoses and microbial surveillance.